Victimization experiences of adolescents in Malaysia - Choo, W.Y.; Dunne, M.P.; Marret, M.J.; Fleming, M.; Wong, Y.L. (2011)
Purpose: There has been little community-based research regarding multiple-type victimization experiences of young people in Asia, and none in Malaysia. This study aimed to estimate prevalence, explore gender differences, as well as describe typical perpetrators and family and social risk factors among Malaysian adolescents. Methods: A cross-sectional survey of 1,870 students was conducted in 20 randomly selected secondary schools in Selangor state (mean age: 16 years; 58.8 female). The questionnaire included items on individual, family, and social background and different types of victimization experiences in childhood. Results: Emotional and physical types of victimization were most common. A significant proportion of adolescents (22.1) were exposed to more than one type, with 3 reporting all four types. Compared with females, males reported more physical, emotional, and sexual victimization. The excess of sexual victimization among boys was due to higher exposure to noncontact events, whereas prevalence of forced intercourse was equal for both genders (3.0). Although adult male perpetrators predominate, female adults and peers of both genders also contribute substantially. Low quality of parent-child relationships and poor school and neighborhood environments had the strongest associations with victimization. Family structure (parental divorce, presence of step-parent or single parent, or household size), parental drug use, and rural/urban location were not influential in this sample. Conclusion: This study extends the analysis of multiple-type victimization to a Malaysian population. Although some personal, familial, and social factors correlate with those found in western nations, there are cross-cultural differences, especially with regard to the nature of sexual violence based on gender and the influence of family structure. (C) 2011 Society for Adolescent Health and Medicine. All rights reserved.